Análisis financiero y proyección de estados financieros en la empresa de servicio de limpieza ULTRACLEANING G&R CIA. Ltda., de la ciudad de Loja, provincia de Loja. Período 2019 al 2021. - González Román, Doris Soraya (2023)
The present thesis work was focused on performing a: Financial analysis and projection of financial statements in the company of Cleaning Service ULTRACLEANING G&R Cía. Ltda. from Loja city, during the period 2019 - 2021. The main objective was to know the financial situation of the company using tools such as: vertical and horizontal analysis and financial ratios, in addition to graphically represent and interpret the results obtained. Pro forma financial statements were prepared and financial evaluation techniques were applied using study methods such as scientific, deductive, inductive, analytical, synthetic, mathematical and statistical, making use of techniques such as observation and interview. The results revealed that accounts receivable from the public sector decreased significantly for the year 2021 and through the analysis of the DUPONT system it was determined that the company had a turnover of 1.48 in the last year. However, it was found that liquidity, profitability and solvency were not optimal. For the preparation of the pro forma financial statements, the average growth method was used, which was corroborated by the company's manager, and the following results were obtained when applying the financial evaluation tools: Net Present Value (NPV) $93,491.65, which indicates that it is acceptable, the Internal Rate of Return (IRR) 12.25%, the Benefit-Cost Ratio indicated that, for every dollar invested, the profit would be 0.10 cents, with an estimated investment recovery time of 10 months and three days. These findings reflect that the NPV is positive, which implies that the investment in machinery is viable for the company. Keywords: Financial analysis, Financial ratios, Projection of financial statements, Investment.